Metamorphic Imagination in Antonio Machado's 'El poeta' - de Ros, X (Maney Publishing, 2010)
The reference to the mythological sea god Glaucus at the beginning of Antonio Machado's 'El poeta' conjures up the protean quality of his poetic vision. Water carries a constant transformative element into Machado's poetry and its imagery prompts some of the most lyrical passages of his work. Whilst this aspect has generally been interpreted in connection with the theme of time, water imagery is also related to a worldview dominated by a sense of indeterminacy and fluidity which has its ultimate source in Ovid's Metamorphoses. This metamorphic imagination is at play in 'El poeta', an important but overlooked early poem included in his collection Soledades. Galerías. Otros poemas. A close analysis of this poem reveals that Machado's meditation on the poet's predicament goes beyond the self-referential framework in which his Symbolist poems tend to be read. While the poem's richly allusive texture highlights Machado's increasing confidence as a poet, its embedded dualism shows his sensibility for paradox - a form of discourse which would underlie his whole poetics. La referencia a Glauco, el mitológico dios marino, en 'El poeta' de Antonio Machado invoca el carácter proteico de su visión poética. El agua conlleva un elemento de constante transformación en la poesía machadiana y sus imágenes dan lugar a algunos de los pasajes más líricos de su obra. Si bien este aspecto se ha interpretado por lo general en relación al tema de lo temporal, las imágenes acuáticas están relacionadas asimismo con una visión dominada por un sentimiento de indeterminación y fluidez que encuentra su fuente última en las Metamorfosis de Ovidio. Esta imaginación metamórfica está presente en 'El poeta', un poema temprano, importante aunque poco estudiado, que figura en su libro Soledades. Galerías. Otros Poemas. Un análisis cabal de este poema demuestra que la meditación de Machado sobre la experiencia del poeta va más allá del marco auto-referencial dentro del cual se tiende a considerar su poesía más simbolista. Mientras que la rica textura alusiva del poema subraya la creciente seguridad de Machado como poeta, su implícito dualismo muestra la sensibilidad de Machado hacia la paradoja — un modo de discurso que va a caracterizar toda su poética.